2021
DOI: 10.1002/dad2.12264
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning improves utility of tau PET in the study of Alzheimer's disease

Abstract: Introduction Positron emission tomography (PET) imaging targeting neurofibrillary tau tangles is increasingly used in the study of Alzheimer's disease (AD), but its utility may be limited by conventional quantitative or qualitative evaluation techniques in earlier disease states. Convolutional neural networks (CNNs) are effective in learning spatial patterns for image classification. Methods 18F‐MK6240 (n = 320) and AV‐1451 (n = 446) PET images were pooled from multiple studies. We performed iterations with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…In other words, it is difficult to classify tau deposition measurements as representative of cognitive decline including MCI and AD compared to CU through the ROIs of stage III/IV. We performed a systematic review of the existing literature to summarize the most common CU versus AD classification techniques that include comparison of CU versus MCI (Table 3 ) 17 , 18 , 22 27 . Notably, the classification between CU and MCI in this study showed better performance than other previously published methods.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, it is difficult to classify tau deposition measurements as representative of cognitive decline including MCI and AD compared to CU through the ROIs of stage III/IV. We performed a systematic review of the existing literature to summarize the most common CU versus AD classification techniques that include comparison of CU versus MCI (Table 3 ) 17 , 18 , 22 27 . Notably, the classification between CU and MCI in this study showed better performance than other previously published methods.…”
Section: Discussionmentioning
confidence: 99%
“…The application of deep learning and ML using Tau-PET has become common in recent years, either to improve PET image acquisition 13 , to classify spatial patterns 14,15 , to study the association between Aβ and Tau-PET scans 16 , or to predict pathological tau accumulation from clinical measures 17,18 . ML-based indices have also been introduced such as Spatial Pattern of Abnormality for Recognition of Early Tauopathy (SPARE-Tau) 19 and Alzheimer's disease resemblance atrophy index (AD-RAI) 20 .…”
Section: Identification Of Positive Tau-pet Scansmentioning
confidence: 99%
“…While a growing number of DL-based clinical applications have been proposed for PET imaging, 15 their use in tau PET imaging has been limited to 18 F-flortaucipir and 18 F-MK-6240 for AD. 16 , 17 , 18 To the best of our knowledge, no studies have investigated the performance of DL algorithms using raw PET images without spatial and intensity normalization as input. In the context of PSP, where elevated tracer uptake mainly occurs in small, deep brain structures such as the subcortical nucleus, Endo et al.…”
Section: Introductionmentioning
confidence: 99%